Strategi Implementasi Pembelajaran Inklusif dan Kesetaraan Gender Pada Mata Pelajaran IPAS di SMK - Isnaeni, Yulia; Prasetyono, Hendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive learning is an approach that guarantees the fulfillment of educational rights for all students, including slow learners with Special Needs (ABK). This study aims to provide an overview of the implementation strategy for inclusive learning for slow learners, as well as to raise awareness for students about the importance of prioritizing gender equality through learning of science subjects in vocational high schools. This study uses a systematic literature review, also known as a Systematic Literature Review (SLR) with the PRISMA method. Data sources in this study use 10 journals and 1 book. The results of this research data are that the strategy for implementing inclusive learning and gender equality in science project learning in vocational schools can be implemented by planning learning that is tailored to the needs of slow learner students, so that there is no more discrimination against in teaching and learning activities with project-based learning so that gender sensitivity and inclusion can be truly measured and instilled in students.